The triumph of the Innocents - Hunt, William Holman, 1827-1910 (Salt Lake City, UT : Project Gutenberg, 2024)
"The Triumph of the Innocents" by William Holman Hunt is an artistic and reflective account based on the biblical narrative of the Flight into Egypt, which is depicted in a painting by the author. Written during the late 19th century, this work explores themes of innocence, compassion, and the profound suffering associated with the Massacre of the Innocents as ordered by King Herod. The book intricately ties historical and theological interpretations with the emotional weight of the events surrounding the Holy Family's escape to Egypt. In this vivid description, Hunt paints a detailed scene where the Holy Family travels in the dead of night, accompanied by the spirits of the innocent children slain by Herod. As Mary and Joseph seek refuge, we witness a powerful juxtaposition between the joy of the holy travellers and the sorrow of the bereaved mothers left behind. Hunt delves into the spiritual significance of this journey, highlighting Mary's compassion for the innocents and the divine mercy bestowed upon them. Through rich imagery and deep symbolism, the narrative emphasizes the connection between suffering, salvation, and hope, ultimately portraying the triumph of innocence amidst grief. (This is an automatically generated summary.)
Release date is 2024-08-03
Produced by Mairi, Donald Cummings and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Christian art and symbolism; Hunt, William Holman, 1827-1910. Triumph of the Innocents